Simplified modeling of electromagnets for dynamic simulation of transient effects for a synchronous electric motor. Issue 1 (17th November 2021) - Bechler, Florian; Kesten, Julius; Wittemann, Florian; Henning, Frank; Doppelbauer, Martin; Eberhard, Peter
Abstract: This study aims to show an approach for the dynamic simulation of a synchronous machine. The magnetic forces in the air gap are calculated efficiently using simplified approaches without neglecting important effects. For the modeling of the magnetic forces, an equivalent magnetic circuit is constructed in which the magnetic saturation and the leakage flux are taken into account and coupled with the electrical circuit at the end. The calculated magnetic forces are then passed to a mechanical model of the motor. Together with a predefinable load torque, the resulting motor rotation and the forces in the bearings are identified. The presented model is then investigated in a small example. This novel approach is intended to provide a method of calculating dynamically the forces transmitted from the shaft to the motor housing and to create the basis for evaluating electric motors for vibrations, noise, and harshness under varying loads and input voltages.